Sistema de ensino e aprendizagem baseado em design: o design da autonomia como metodologia educacional - SILVA, Anderson Luis da (2019)
The research starts from the assumption that man, in the set of his theoretical and technical competences, suffered as a result of social determinations resulting from the socioeconomic and cultural events arising from the historical period defined by Modernity, among them the Illuminist Movement, the Industrial Revolution and the institution of the compulsory School, a process of operational circumscription and productive autonomy. In this way, this man has a more and more distanced and intermediated relationship between his imperatives to the maintenance of life and the way in which he articulates his attainment. It was understood that, due to this condition and against a present and future context that calls for a pressing exhaustion of resources and material and immaterial conditions necessary for the maintenance of the industrial production and consumption system, such as those implemented under the auspices of the Capitalism, the need for effective action in the development processes and theoretical, technical and technological appropriation improvement due to the incipient local and global contextual demands. It was promoted by means of a survey and theoretical relational analysis based on the writings and researches of authors in the areas related to the study, and in their relations with contemporary teaching and learning practices, whether based on historical traditionalism or methodological disruption and procedural, the formulation of a system of teaching and learning that allows the development of the design of autonomy as elemental competence in the formation of individuals for the 21st century.